Efficacy and safety of using eslicarbazepine in treating focal epilepsy in clinical practice (based on international Euro-Esli study and personal experience) - I. A. Zhidkova; V. A. Karlov; P. N. Vlasov (Эпилепсия и пароксизмальные состояния)
The latest data on the eslicarbazepine (ESL) efficacy, tolerability and safety in treatment of focal epilepsy are presented based on the results of the European study in clinical practice Euro-Esli that enrolled 2058 patients from 14 European centers, a detailed subgroup analysis, as well as our own data on the follow-up of 65 patients with focal epilepsy receiving ESL in monotherapy or combination therapy.According to the Euro-Esli study, a 12-months follow-up allowed to conclude that therapy retention comprised 73.4%; percentage of responders was 75.6%, whereas proportion of patients with complete seizure cessation was 41.3 %. Regarding ESL efficacy it may be concluded that our personal data were comparable to those obtained during the international study Euro-Esli so that retention was 80%; percentage of responders was 75.4%, whereas seizure-free rate was 58.5%. As for the ESL safety profile our study demonstrated that adverse events (AEs) were registered at lower rate in as few as 21.5% of patients compared to 34% found in the Euro-Esli study. No unexpected serious AEs during the long-term follow-up period were documented in the both studies, which evidence about favorable ESL safety profile elderly patients, patients with comorbid intellectual and mental disorders as well as patients with post-stroke epilepsy.